Human dignity and sexual behavious – A theological perspective - Vorster, Nicolaas (Verbum et ecclesia, 2005)
This article compares the sex ethic of Scripture with the anthropological values that underlie modern sexual morality and gives guidelines for a responsible sex ethics that can safeguard human dignity. As point of departure it states that the biblical view of sexuality must be understood from the perspective of creation and re-creation and not the fall. The creation narratives teach that humanity possesses qualities of sameness and difference that constitutes our being. Sexuality forms the dynamic which bonds the dialectic of sameness and difference into a unity of persons. The article concludes that the African concept of gender , the radical freedom concept of secular society, the utilitarian view of sex, and the postmodern view that sexual behaviour and marriage are social constructs, aggravate sexual promiscuity. In order to fight HIV/AIDS and preserve human dignity the exclusiveness of the sex act, the importance of faithfulness and the sanctity of marriage must be proclaimed.